(E)-2-(5-Chloro-2-hydroxybenzylidene)-N-cyclohexylhydrazine- 1-carbothioamide - Arafath, Md. Azharul; Adam, Farook; Razali, Mohd Rizal (International Union of Crystallography, 2017)
In the title compound, C 14 H 18 ClN 3 OS, the phenol ring is almost coplanar with the hydrazinecarbothioamide moiety, making a dihedral angle of 6.92 (8)°. The cyclohexane ring has a chair conformation and the conformation about the C=N bond is E . In the crystal, molecules are linked by N—H...O and O—H...S hydrogen bonds, forming inversion dimers with an R2² (14) ring motif flanked by two R2² (6) ring motifs. The dimers are linked by short Cl...Cl interactions, forming layers parallel to the ab plane.